Pravni vidiki odvzema volkov iz narave z odstrelom zaradi preprečevanja resne škode - Štemberger Brizani, Katja (Pravnik, 2024)
The paper discusses the legal aspects of culling wolves as a measure to prevent serious harm, with a focus on (recent) case law of the Court of Justice of the European Union regarding the conditions under which culling is permissible. It analyses three recent decisions of the Ministry of Natural Resources and Spatial Planning regarding the wolf culls. This analysis considers the Guidelines for Proving the Conditions for the Removal of Wolves from the Wild by Culling, aiming to determine whether administrative practice has changed or improved following the latest relevant decisions of the Administrative Court and the Constitutional Court of the Republic of Slovenia. The article also examines various legal quandaries presented the current regulation on the wolf removal in the Regulation on Protected Wildlife Species. It questions the compatibility of these regulations with the principle of legality and debates the suitability of enacting the measure of wolf removal through a by-law, specifically a government decree.
Keywords: conditions for wolf culling; dovoljenje; habitatna direktiva; Habitats Directive; načelo zakonitosti; permit; pogoji za odstrel volkov; precautionary principle; preprečevanje resne škode na premoženju; prevention of serious damage to property; previdnostno načelo; principle of legality; Regulation on protected wildlife species; Uredba o zavarovanih prostoživečih živalskih vrstah